Effects and central mechanism of electroacupuncture and MRI-navigated rTMS for PSD: study protocol for an fMRI-based single-center, randomized, controlled, open-label trial - Lu, Hai; Wang, Yang; Shen, Diwen; Ruan, Jianguo; Lu, Jiaming; Wang, Linlin; Song, Yang; Fan, Jia; Li, Dongna; Shi, Lijing; Xia, Meng; Xu, Tianshu (Frontiers in Psychiatry, 2024)
Post-stroke depression (PSD) is the most common mental complication after stroke and has a serious impact on functional outcomes and quality of life for stroke patients. Antidepressants are the first-line treatment for PSD, but many reported side effects remain. Clinical research and practice guidelines have shown that electroacupuncture(EA) or rTMS has a positive effect on PSD. However, there are few clinical studies on EA and MRI-navigated rTMS for PSD to explore its fMRI-based central mechanism on depression.In this randomized, controlled, open-label trial, sixty-four patients with PSD will be randomly allocated into the experiment group (n=32) or control group (n=32). The experiment group will receive EA and MRI-navigated rTMS, and the control group will receive MRI-navigated rTMS treatment, in 12-20 sessions over 4 weeks. In addition, ten healthy people for fMRI scanning will be recruited as a healthy control group without any intervention. The primary outcome is the change from baseline in the Hamilton Depression Scale-24 items (HAMD-24) scores at week 4. The primary analysis of central mechanism mainly involves cortical morphology, local spontaneous brain activity, and default mode network (DMN) functional connectivity based on fMRI at 0-wk and 4-wk. Secondary outcomes include the neuro-patho-physiological and quality of life changes in cortical excitability with motor evoked potential test(MEP), National Institutes of Health Stroke Scale(NIHSS), EuroQol Five Dimensions Questionnaire (EQ-5D) Scale, Modified Barthel Index(MBI) Scale and Health Scale of Traditional Chinese Medicine(HSTCM). Additional indicators include the Acceptability Questionnaire and Health Economics Evaluation (cost-effectiveness analysis) to assess acceptability and economic practicality of the treatment in study. Outcomes are assessed at baseline and post intervention. Discussion: EA and MRI-navigated rTMS therapy could become an alternative treatment for PSD, and it is expected that this trial will provide reliable clinical evidence and potential central mechanism for the future use of EA and MRI-navigated rTMS for PSD. Clinical trial registration: NCT05516680(ClinicalTrials.gov, registered in August 2022).